2012
DOI: 10.1248/bpb.b12-00200
|View full text |Cite
|
Sign up to set email alerts
|

Elcatonin in Combination with Risedronate Is More Effective than Risedronate Alone for Relieving Back Pain in Postmenopausal Women with Osteoporosis

Abstract: Intramuscularly administered elcatonin (ECT) reduces pain via the central nervous system. A prospective study was performed to determine whether ECT has a beneficial effect on back pain and function in postmenopausal women with osteoporosis during bisphosphonate therapy. Sixty-one postmenopausal osteoporotic women with back pain (mean age: 73.7 years, range: 54-96 years) were divided into two groups: the control group (n 30) and the ECT (intramuscular, 20 units a week) group (n 31). All patients received treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…29 However, postmenopausal osteoporotic patients with no fractures also suffer from chronic pain, which may be related to osteoclastic bone resorption. 30 Osteoclasts dissolve bone minerals by releasing protons through the a3 isoform of the vacuolar H + -ATPase (a3V-ATPase) and creating acidic microenvironments, which can activate the ASIC and TRP proteins. 31 Previous studies have demonstrated that the activation of ASIC3 and TRPV1 and the release of CGRP play important roles in acute inflammatory, chronic neuropathic and cancer pain.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, postmenopausal osteoporotic patients with no fractures also suffer from chronic pain, which may be related to osteoclastic bone resorption. 30 Osteoclasts dissolve bone minerals by releasing protons through the a3 isoform of the vacuolar H + -ATPase (a3V-ATPase) and creating acidic microenvironments, which can activate the ASIC and TRP proteins. 31 Previous studies have demonstrated that the activation of ASIC3 and TRPV1 and the release of CGRP play important roles in acute inflammatory, chronic neuropathic and cancer pain.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Iwamoto et al presented data from a 5-year-period study demonstrating a sustainable role of ECT in post-menopausal women with osteoporosis [ 22 ]. In addition, another study in post-menopausal osteoporotic women confirmed the active effects of short-term combined treatment with bisphosphonate and ECT on lumbar BMD and bone turnover with back pain [ 23 , 24 ]. Furthermore, mild suppression of callus remodeling by ECT did not impair overall fracture healing process in the femoral fracture model of cynomolgus monkeys [ 9 ], whereas ECT facilitated osteoblast proliferation in the fracture site and suppressed the systemic acceleration of bone resorption without affecting cortical bone regeneration after drill-hole injuries in mice [ 10 ].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the concerns of anti-osteoporosis effects by ECT have been interpreted in the literatures [ 9 , 10 , 22 24 ]. For instance, Iwamoto et al presented data from a 5-year-period study demonstrating a sustainable role of ECT in post-menopausal women with osteoporosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients presenting clinically with osteoporosis is increasingly common; a major hazard of osteoporosis is the associated increased risk of fracture and the potential induction of numerous other complications (2). It has been shown in epidemiological investigations that osteoporosis has become a common disease in clinics, and the importance of its associated risks has been increasingly recognized by clinicians (2,3).…”
Section: Introductionmentioning
confidence: 99%